2022
DOI: 10.1123/japa.2020-0343
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of a Biography-Based Physical Activity Intervention in Institutionalized People With Dementia: Quantitative and Qualitative Results From a Randomized Controlled Trial

Abstract: The objective of this multicenter randomized controlled trial was to evaluate the feasibility and effectiveness of a physical activity intervention for institutionalized people with dementia, individualized by capacity and biography. The intervention group (n = 34; age: mean = 86.09 years; 79.40% female; mean Mini-Mental State Examination value = 18.59) participated in a multicomponent training program, which included daily activities, dancing, gardening, and sports/games, twice weekly for 3 months. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 83 publications
3
6
0
Order By: Relevance
“…We considered it important to include other types of dementia because exercise has been proven to be beneficial not only in AD [14,15,18,[21][22][23][24][25]. The mean age of the patients (74.2 years old in the intervention group) is in agreement with other studies that have reported a mean age of participants lower than 80 [14,17,[19][20][21]26], while we also found others with that greater than 80 [16,18,[22][23][24][25][27][28][29].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…We considered it important to include other types of dementia because exercise has been proven to be beneficial not only in AD [14,15,18,[21][22][23][24][25]. The mean age of the patients (74.2 years old in the intervention group) is in agreement with other studies that have reported a mean age of participants lower than 80 [14,17,[19][20][21]26], while we also found others with that greater than 80 [16,18,[22][23][24][25][27][28][29].…”
Section: Discussionsupporting
confidence: 87%
“…Other assessment tools have also been used to measure the risk of falls and physical capacities in people with dementia: the Berg balance scale [15,21], number of falls in a period of time [19,28], frailty and injuries: cooperative studies of intervention techniques-subtest 4 (FICSIT-4) [18,27], the 6 min walk test [18,27], and the functional independence measure (FIM) [19,20]. In our study, we also used valid and reliable instruments to measure the risk of falls and functional capacities, in agreement with other studies that used TMT [21] and SPPB [16,20,27,29] in their assessments.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations